Pengaruh Penyajian Visual Dan Gaya Bahasa Pada Video Tentang Pariwisata Di Kabupaten Garut Terhadap Peningkatan Pengetahuan - Testa Pradia Nirwana; Amiruddin Saleh; Krishnarini Matindas (Institut Pertanian Bogor, 2016)
Tourism is one of sectors that is much enthused by the world community, this demand has increased annually. Garut is one of the districts in West Java which is interested by tourists. Furthermore, the promotion for the tourism product roles the prominent for the development of communities and regions. The promotion can use media of video through social media. This media is used to provide an illustration and the knowledge of tourism, and convince young travelers to visit the tourist attraction which is offered. The purpose of this study involves 1) to test the effect of visual presentation and style of language through video in increasing students’ knowledge, 2) to analyze the most effective message combination on the media of video about tourism in Garut regency, 3) to analyze the relationship between individual characteristics with improvement knowledge of students. This study employed true experimental methods with 2 x 2 factorial design by using pretest posttest control group design. Dealing with this, factors are used in the visual presentation consists of photos and infographics, and the language style consists of formal and conversational forms. The subjects participating in this study are 75 students of Bogor Agricultural University. The result of this study confirms that the visual presentation and the language style through video have significant influence on the increase of knowledge. The whole combination of treatment is not significantly different from the improvement of knowledge, and the individual characteristics are not significantly related to the improvement knowledge.Keywords: improvement knowledge, language style, video tourism, visual presentation